Effects of the A+ intervention on elementary-school teachers’ social and emotional competence and occupational health - Oliveira, Sofia; Roberto, Magda Sofia; Veiga-Simão, Ana Margarida; Marques-Pinto, Alexandra (Frontiers in Psychology, 2022)
Teaching has been described as a high-risk profession as far as teachers’ occupational health and well-being is concerned, due to the high professional demands of a social and emotional nature that characterize their daily lives. Hence, the design of interventions explicitly designed for in-service teachers with a view to promoting their social and emotional competence is particularly important, since they positively impact teachers’ well-being and personal accomplishment and contribute to a decrease in their psychological distress, namely emotional exhaustion. The present study aimed to evaluate the effectiveness of the A+, an online social and emotional learning intervention for elementary-school teachers. It also sought to assess the quality of the intervention's implementation. A quasi-experimental study was conducted with a total of 81 participants (96.3% female, MAge = 46.21, SDAge = 4.82, n = 42 assigned to the experimental group) from three different school contexts. Data regarding the efficacy of the A+ was collected across four waves using a set of self-report questionnaires that assessed proximal variables (i.e., social and emotional skills) and distal variables (e.g., well-being, burnout symptoms). Robust linear mixed models were used to analyze the data. Additionally, two trained observers completed an observation grid to evaluate the quality of the A+ implementation (e.g., participant responsiveness, fidelity). Results suggested that, over time, the A+ had positive impacts across proximal (e.g., increased self-regulation, positive relationship, conflict management skills) and distal variables (e.g., increased emotional well-being, decreased occupational stress and emotional exhaustion symptoms) favoring the experimental group. However, results differed across the school contexts. These findings were accompanied by excellent implementation quality indicators, namely high fidelity in the delivery of the A+ contents and high participants’ responsiveness. Despite its limitations, this study contributes to a growing body of research which reinforces the importance of investing in social and emotional learning interventions to prevent teachers’ burnout and improve their occupational health. Furthermore, it highlights the importance of implementation quality research as a component of program planning with a view to enhancing programs’ efficacy, as well as the need to adapt and consider context variables in research and practice.